Withdrawal of Staphylococcus aureus from intensive care units in Turkey - Erdem, Hakan; Dizbay, Murat; Karabey, Selma; Kaya, Selcuk; Demirdal, Tuna; Koksal, Iftihar; Unal, Serhat (Mosby-Elsevier, 2013)
Background: In the past, Staphylococcus aureus infections have displayed various patterns of epidemiologic curves in hospitals, particularly in intensive care units (ICUs). This study aimed to characterize the current trend in a nationwide survey of ICUs in Turkey. Methods: A total of 88 ICUs from 36 Turkish tertiary hospitals were included in this retrospective study, which was performed during the first 3 months of both 2008 (period [P] 1) and 2011 (P2). A P value <=.01 was considered significant. Results: Although overall rates of hospital-acquired infection (HAI) and device-associated infection densities were similar in P1 and P2, the densities of HAIs due to S aureus and methicillin-resistant S aureus (MRSA) were significantly lower in P2 (P < .0001). However, the proportion of HAIs due to Acinetobacter was significantly higher in P2 (P < .0001). Conclusions: The incidence of S aureus infections is declining rapidly in Turkish ICUs, with potential impacts on empirical treatment strategies in these ICUs. Copyright (C) 2013 by the Association for Professionals in Infection Control and Epidemiology, Inc. Published by Elsevier Inc. All rights reserved.
Keywords: Staphylococcus; Epidemiology; Incidence; Critical